Photochromic and photomodulated luminescence properties of two metal–viologen complexes constructed by a tetracarboxylate-anchored bipyridinium-based ligand. Issue 41 (14th September 2018) - Li, Lin-Ke; Li, Hai-Yang; Li, Ting; Quan, Li-Hong; Xu, Jing; Li, Fu-An; Zang, Shuang-Quan
Abstract : Photochromic and photomodulated luminescence properties of two metal–viologen complexes constructed using a tetracarboxylate-anchored bipyridinium-based ligand are reported. Abstract : In this study, two metal–viologen complexes, formulated as [Cd1.5 (H2 L)0.5 (Cl)3 (CH3 OH)] n (1 ) and [Eu2 (L)(NO3 )4 (HOCH2 CH2 OH)2 ] n (2 ), were constructed by a tetracarboxylate anchored bipyridinium-based ligand 1, 1′-bis(3, 5-dicarboxybenzyl)-4, 4′-bipyridinium dichloride (H4 L·Cl2 ). Single-crystal X-ray analyses revealed that complex1 featured a 2D-layered structure, while complex2 showed a 1D "ladder-like" chain structure. The difference in the central metal ions, anions, solvent molecules, deprotonation degree of the tetracarboxylate ligand, coordination modes and conformations of the ligand have a great influence on the final structure. As expected, incorporation of the viologen moiety to the frameworks led to the predefined photochromism: when samples1 and2 were exposed to UV-visible light, a reversible color change from light yellow to blue/dark blue occurred. Moreover, complex2 exhibited the characteristic emission of Eu(iii ) ion in the visible region, and it also displayed an interesting reversible tunable photo-induced luminescence switching behavior: under the irradiation of UV-vis light, the luminescence emission intensity of complex2 gradually decreased and reached 15% of the starting value after 8 min. These results may not only help to further understand the structure–photoresponse relationships of viologen-based MOFs, but also help to guide the design and synthesis of luminescent materials with photo-modulated switching ability.